Serial changes in left ventricular myocardial deformation in sepsis or septic shock using three-dimensional and two-dimensional speckle tracking echocardiography - Yan, Xiaojun; Li, Yuman; Liu, Juanjuan; Zhou, Ting; Zhou, Yi; Sun, Wei; Sun, Chenchen; Ma, Jing; Zhang, Li; Shang, You; Xie, Mingxing (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed to investigate the serial changes in left ventricular (LV) myocardial deformation in patients with sepsis using three-dimensional (3D) and two-dimensional (2D) speckle tracking echocardiography (STE). Methods: In this single-centered, prospective, and observational study, we included 59 patients diagnosed with sepsis or septic shock in the intensive care unit and 40 healthy controls. Left ventricular ejection fraction (LVEF), left ventricular global longitudinal strain (GLS), and global circumferential strain (GCS) assessed by 3D-STE and 2D-STE were obtained on the 1st, 3rd, 5th, 7-10th days after sepsis or septic shock. Results: In patients with sepsis or septic shock, 3D and 2D-LVEF were not different among the each time point. GLS and GCS obtained by 3D-STE and 2D-STE decreased on the 1st day compared with the healthy group (all P < 0.01). Compared with the values on the 1st day, GLS and GCS further decreased on the 3rd day, while 3D- and 2D-LVEF did not differ. 3D- and 2D-STE strains were lowest on the 3rd day, and gradually improved on the 7-10th day compared with values on the the 3rd day. When comparison with values on the 1st day, 3D- and 2D-GLS gradually improved on the 7-10th day, whereas 3D- and 2D- GCS on the 7–10th day was not different. Although 3D- and 2D-STE strain were significantly increased on the 7–10th day, they were not fully recovered to normality. Conclusion: Although patients with sepsis or septic shock demonstrated gradual improvements in 3D and 2D-STE parameters during the 10-day period, LV myocardial strain was not fully recovered to normality on the 7–10th day. 3D and 2D strain imaging used as a helpful tool for monitoring the evolution of myocardial deformation can provide clinicians with a useful additional imaging parameter.